(untitled) (International Seven Journal of Multidisciplinary, 2024)
In Mexico, drug trafficking is no longer the main source of income for criminal organizations, since the increase in the production, distribution and consumption of synthetic narcotics, such as opioids or amphetamines, has displaced plant-based drugs such as marijuana or opium gum obtained from poppy flowers from the market, as well as the legalization of cannabis in different states of the United States. This business seems to be becoming unsustainable for the Mexican cartels, which did not take long to move into a more lucrative business. Organized crime has diversified its criminal activities, mainly through extortion by charging "derecho de piso" or "criminal tax" to all types of businesses. In this way, criminal groups have found in extortion not only a way to regulate everything that can produce capital, but also to recover the profits that the decline in the trafficking of plant-based drugs left them with after the increase in the consumption and trafficking of synthetic drugs. Currently, the term organized crime has been used to refer to groups of people dedicated to trafficking drugs, people, kidnappings, murders, among other crimes. In addition, it has diversified its operations, entering into legal businesses to operate them illegally. Organized crime continues to advance in extortion and disappearances, there is a trend in the disappearance of men to force them to join organized crime and in the case of women to take them to the trafficking market. Extortion and disappearances are two indicators where there is a 45% increase in complaints. Criminal groups have affected the food supply chain, increasing the prices of basic products such as tomatoes, serrano peppers, lemons, corn and avocados. In addition, they have made inroads into the fishing, transportation and other sectors, generating losses in the millions and affecting the daily lives of Mexicans, with an increase in violence and insecurity. All these illegal activities related to the financing of organized crime structures with high economic profitability and with links to different types of violence and corruption, is what is called criminal economy.